Numerical analysis of Al2O3 Nanofluids in serpentine cooling plate of PEM fuel cell / Irnie Azlin Zakaria...[et al.] - Zakaria, Irnie Azlin; Wan Mohamed, Wan Ahmad Najmi; Mohd Ihsan Mamat, Aman; Sainan, Khairul Imran; Mat Nawi, Muhad Rozi; Najafi, Gholam Hassan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
PEM fuel cell converts the energy potential of a hydrogen based fuel into electricity with water and heat as the major by-products. In order to optimize the performance of a PEM fuel cell, the cooling system is responsible to manage the accompanying heat. In this study, heat transfer and fluid flow performance of Aluminium oxide, Al2O3 nanofluids in a serpentine cooling plate is investigated numerically. The Al2O3 nanofluids concentration of 0.1%, 0.3% and 0.5% was dispersed in both water and 60:40 and 50:50 water:ethylene glycol (w:EG) mixture of base fluids. The thermo-physical properties of the prepared nanofluids namely thermal conductivity and viscosity were measured and then fed to the simulation to enable maximum accuracy to the real experimentation result. A steady and incompressible flow with constant heat flux is assumed in the carbon graphite channel of 210mm x 220mm. All characteristics studied is at Re number range of 150 to 400. A serpentine cooling plate is used to mimic a single cooling plate in a complete stack of PEM fuel cell. The simulation used was ANSYS Fluent in laminar flow condition. The result shows that the heat transfer coefficient of 0.5 % volume concentration of Al2O3 in 100:0(w:EG) has increased up to 37 % as compared to base fluid. The increase in pumping power is experienced but at a much lower value as compared to the thermal management advantage.